Analisis Hukum Susuan Dalam Hadis Ditinjau Perspektif KHI Pasal 39 Tentang Larangan Kawin - Ridha, Aisyatur; Ramadhona, Suci (Institut Syekh Abdul Halim Hasan Binjai, 2024)
This study analyzes the law of breastfeeding in hadith from the perspective of Article 39 of the Compilation of Islamic Law (KHI), which regulates marriage prohibitions. The law of breastfeeding is explicitly outlined in the hadiths of Prophet Muhammad (PBUH), which establish that a mahram status is created after five complete feedings by a baby, forming the basis for the prohibition of marriage between those related by breastfeeding. Furthermore, Article 39 of the KHI reinforces this principle by stating that breastfeeding relations hold the same status as kinship relations concerning marriage prohibitions. Through a normative-juridical approach, this study finds that breastfeeding regulations serve to maintain clarity in lineage and family structure, as well as prevent prohibited marriages in Islam. Therefore, both in the hadith and the KHI, breastfeeding law plays a crucial role in protecting family integrity and lineage, while upholding the principles of mahram (non-marriageable kin) in Islam.